A small Multi-site Higher Education Institution Managing Change in its e-learning Culture - Cunningham, Kellie; Greenwood, Anthony; Howard, James; Inman, Jane; Johnson, Samuel; Marcangelo, Caroline; Weaver, Margaret (Proceedings of the International Conference on Networked Learning, 2006)
This paper and associated poster report on the participant-observation of a project team working in a multi-site Higher Education institution in north-west England. The team was set up to create an action plan for the enhancement of flexible and distributed learning but as the project progressed it became clear that this was not an appropriate target. The paper reflects on the project team’s engagement with the Higher Education Academy’s “Change Academy” programme, its influence on their working methods and intended outcomes.